REGULATION OF THE EXPIRATION OF THE FISHING PERMIT AND OF THE OPERATING LICENSE OF PROCESSING PLANTS IN THE GENERAL FISHERIES LAW AND ITS REGULATIONS - Oblitas Sánchez, Nery Yanet (2019)
The present paper is intended to make known the regulation of the expiration in the General Fishing Law, Decree Law No. 25977, and its Regulations, approved by Supreme Decree No. 012-2001-PE, and in which cases it is necessary to declare it, specifically with regard to the fishing permit and the operating license of processing plants. In effect, the way in which the expiration is regulated and the reasons for which the Administration proceeds to declare it, as well as its nature, is set forth.